Welcome - Jeffers, Joshua (The Toro Historical Review, 2025)
Welcome to volume 16, issue 1 of The Toro Historical Review! This issue features seven essays produced in upper-division history classes and represents remarkable achievements in undergraduate research, writing, and editing. Well done all! Congratulations to the authors: Samantha Chavez, Lauren Heib, Ava Kostka, Lance Lee, John Robbins, Johanna Villalobos And a special thank you to our editorial team who has worked hard to bring this issue to fruition. Thank you!